Advances in Ferroelectrics - Peláiz Barranco, Aimé (IntechOpen, 2012)
Ferroelectricity is one of the most studied phenomena in the scientific community due the importance of ferroelectric materials in a wide range of applications including high dielectric constant capacitors, pyroelectric devices, transducers for medical diagnostic, piezoelectric sonars, electrooptic light valves, electromechanical transducers and ferroelectric random access memories. Actually the ferroelectricity at nanoscale receives a great attention to the development of new technologies. The demand for ferroelectric systems with specific applications enforced the in-depth research in addition to the improvement of processing and characterization techniques. This book contains twenty two chapters and offers an up-to-date view of recent research into ferroelectricity. The chapters cover various formulations, their forms (bulk, thin films, ferroelectric liquid crystals), fabrication, properties, theoretical topics and ferroelectricity at nanoscale.